Salvage surgery for advanced non‐small cell lung cancer after targeted therapy: A case series. Issue 4 (28th February 2020) - Song, Weian; Di, Shouyin; Liu, Junqiang; Fan, Boshi; Zhao, Jiahua; Zhou, Shaohua; Chen, Siyu; Dong, Hai; Yue, Caiying; Gong, Taiqian
Abstract: Background: Tumor recurrence or residual tumor after targeted therapy is common in patients with advanced non‐small cell lung cancer (NSCLC). There is a lack of high‐level evidence on which type of treatment should be employed for these patients and the role of salvage surgery has not been well reported in the literature. Methods: A retrospective analysis of patients who underwent salvage surgery in our center between January 2016 and June 2019 for advanced NSCLC after targeted therapy was performed. Results: A total number of nine patients were identified, including five males and four females, with a median age of 56 years (range, 40–65 years), all diagnosed with lung adenocarcinoma stage IIIa–IVb. All patients had received targeted therapy according to individual positive mutation of driver gene(s). Salvage surgery was performed for tumor recurrence or residual tumor after a duration of 2–46 months of targeted therapy. A negative surgical margin was achieved in all cases. Postoperative complication rate was 11.1% (1/9). All patients were alive at the time of this analysis and two patients had disease progression. After a median follow‐up of 17 months (range: 5–44 months), the median event‐free survival and postoperative survival was 14 months (range: 2–44 months) and 17 months (range: 5–44 months) respectively. Conclusions: Salvage surgery may be a feasible and promising therapeutic option for tumor recurrence or residual tumor in advanced NSCLC in selective patients after targeted therapy. Key points: Salvage surgery is feasible in selected patients with advanced NSCLC and provides promising survival outcomes after targeted therapy failure. Salvage surgery provides precise molecular and pathological information which is most important for subsequent therapy.